Needless needle nuisances in Nepal. (March 2020) - Atreya, Alok; Nepal, Samata
Pin-prick injuries which prove not to be infected may still cause fear and distress, but allow the victims, who are often young women, no opportunity for redress. These attacks are causing panic among the targeted population who fear AIDS.